(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper deals with the security related issues in E-Commerce for the online users. It explains the basic scenario of E-commerce working and explains the security concept in online transactions. It also explains the security methods used by E-business sites. It also explains the most frequently questions raised by the users and provides the solutions for their queries.